Pelestarian Penyu kepada Generasi Muda Untuk Keberlanjutan Satwa Langka di Kawasan Sanur, Denpasar, Bali - Kadek Ayu Ekasani; I Gusti Ayu Melistyari Dewi; Ni Made Ayu Natih Widhiarini; Ida Ayu Gayatri Kesumayathi; I Wayan Wiarta (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Turtles as one of the rare and almost extinct animals need to be preserved. The prevention effort taken is through conservation. Conservation cannot work alone without the support of the surrounding community. For this reason, there is a need for public awareness of the importance of preserving turtles. Community service activities by IPB International lecturers and students were carried out in the Sanur area, Denpasar, Bali. The activities are giving counseling about turtle conservation as well as activities to clean up the beach area. Counseling was given by a manager from the turtle sanctuary conservation. There are three stages carried out in this activity, namely the preparation, the counseling, and the cleaning stages. In the preparation stage, the team approached community supervisory groups, fishermen groups, and youth groups in Sanur. Next, the counseling stage was carried out with material about the life cycle of turtles and the process of caring for them. In the final stage, the beach area is cleaned to create a comfortable place for turtles that lay their eggs and hatch on the coast. This community activity is felt to be very beneficial for the young generation who live around the Sanur Beach area. In the future, the community hopes that the team will carry out similar activities in other tourism sectors that can benefit the community in the Sanur area.